THE ROLE OF ADIPOKINES IN PATIENTS WITH CORONARY ARTERY DISEASE. (April 2021) - Papadopoulos, Dimitrios; Sanidas, Elias; Tsakalis, Konstantinos; Velliou, Maria; Zerva, Kanella; Ntaliou, Liana; Iliopoulos, Dimitrios; Mantzourani, Marina; Nikiteas, Nikolaos; Barbetseas, John
Abstract: Objective: Several adipose tissue bioactive factors (adipokines) have been linked to atherosclerosis, namely adiponectin, apelin and omentin-1 prevent atherosclerosis whereas resistin, visfatin and chemerin predispose to the development of coronary atherosclerotic plaques. The aim of this study was to calculate adipokines plasma levels in patients with and without angiographically established coronary artery disease (CAD) investigating any potential corellation between them and CAD. Design and method: Overall, 80 patients (40 with significant CAD and 40 without significant CAD) were studied. Adiponectin, apelin, omentin-1, resistin, visfatin and chemerin plasma levels were measured by the Elisa method. Results: Adiponectin, apelin and omentin-1 plasma levels were significantly lower in patients with CAD whereas visfatin, resistin and chemerin levels were significantly higher compared to those without CAD (Figure). No significant differences in demographic characteristics were observed between the two groups (Table). Figure. No caption available. Conclusions: In patients with angiographically established CAD cardioprotective adipokines were lower while non-cardioprotective adipokines were higher indicating a direct relationship of these factors with the progression of atherosclerosis.